Stability optimization of energetic particle driven modes in nuclear fusion devices: the FAR3d gyro-fluid code - Varela, J.; Spong, D.; Garcia, L.; Ghai, Y.; Ortiz, J.; , FAR3d project collaborators; Adulsiriswad, P.; Aiba, N.; Ascasíbar, E.; Azegami, A.; Bader, A.; Baruzzo, M.; et al. (Frontiers in Physics, 2024)
The development of reduced models provide efficient methods that can be used to perform short term experimental data analysis or narrow down the parametric range of more sophisticated numerical approaches. Reduced models are derived by simplifying the physics description with the goal of retaining only the essential ingredients required to reproduce the phenomena under study. This is the role of the gyro-fluid code FAR3d, dedicated to analyze the linear and nonlinear stability of Alfv én Eigenmodes (AE), Energetic Particle Modes (EPM) and magnetichydrodynamic modes as pressure gradient driven mode (PGDM) and current driven modes (CDM) in nuclear fusion devices. Such analysis is valuable for improving the plasma heating efficiency and confinement; this can enhance the overall device performance. The present review is dedicated to a description of the most important contributions of the FAR3d code in the field of energetic particles (EP) and AE / EPM stability. FAR3d is used to model and characterize the AE / EPM activity measured in fusion devices as LHD, JET, DIII-D, EAST, TJ-II and Heliotron J. In addition, the computational efficiency of FAR3d facilitates performing massive parametric studies leading to the identification of optimization trends with respect to the AE / EPM stability. This can aid in identifying operational regimes where AE / EPM activity is avoided or minimized. This technique is applied to the analysis of optimized configurations with respect to the thermal plasma parameters, magnetic field configuration, external actuators and the effect of multiple EP populations. In addition, the AE / EPM saturation phase is analyzed, taking into account both steady-state phases and bursting activity observed in LHD and DIII-D devices. The nonlinear calculations provide: the induced EP transport, the generation of zonal structures as well as the energy transfer towards the thermal plasma and between different toroidal / helical families.Finally, FAR3d is used to forecast the AE / EPM stability in operational scenarios of future devices as ITER, CFETR, JT60SA and CFQS as well as possible approaches to optimization with respect to variations in the most important plasma parameters.